Tuna Bone Waste (Thunnus sp.) as a Hydroxyapatite Source: Synthesis and Characterization for Biomaterial Applications - Malau, Nya Daniaty (Asian Journal of Advanced Research and Reports, 2025)
Tuna fish bone waste, a by-product of fish processing, exhibits promising potential for conversion into hydroxyapatite (HA), a high-value biomaterial with medical applications. This study successfully synthesized HA from tuna bone waste through a combined approach of calcination (900°C, 10 hours) and wet precipitation using (NH₄)₂HPO₄ at a Ca/P ratio of 1.67. The process achieved a conversion efficiency of 33.97%, producing HA with 81.7% phase purity along with a secondary whitlockite phase (18.3%) attributed to low pH conditions and Mg²⁺ ion presence. Comprehensive characterization revealed: (1) a hexagonal HA crystal structure with lattice parameters a = 9.424 Å and c = 6.879 Å (XRD analysis), and (2) spherical small particles (200-1000 nm) displaying agglomeration tendencies (SEM observation). The synthesized material demonstrates suitable characteristics for biomedical applications including bone grafts and tissue engineering scaffolds. This research presents an eco-friendly strategy for valorizing fishery waste while decreasing reliance on costly synthetic HA sources. Future studies should focus on optimizing the synthesis process to enhance both yield and purity.